2017
DOI: 10.1016/j.fertnstert.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D intake and serum levels with fertility: results from the Lifestyle and Fertility Study

Abstract: Objective To evaluate the role of vitamin D intake and serum levels on conception of clinical pregnancy and live birth. Design Prospective cohort study. Setting Academic medical centers. Patient(s) Healthy, nulliparous women, aged 18-39 years and their male partners. Intervention(s) None. Main Outcome Measure(s) Clinical pregnancy and live birth were compared between those who did or did not meet the vitamin D Estimated Average Requirement (EAR) intake (10 μg/d), and with serum 25(OH)D considered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 44 publications
2
32
0
4
Order By: Relevance
“…Several reports show an association of vitamin D deficiency with increased risk of mortality [ 40 ], cancer (particularly colon, prostate, and breast cancer) [ 41 ], cardiovascular disease [ 42 ], type 1 and type 2 diabetes [ 43 ], autoimmune diseases [ 44 ], and decreased fertility [ 45 ].…”
Section: Clinical Issuesmentioning
confidence: 99%
“…Several reports show an association of vitamin D deficiency with increased risk of mortality [ 40 ], cancer (particularly colon, prostate, and breast cancer) [ 41 ], cardiovascular disease [ 42 ], type 1 and type 2 diabetes [ 43 ], autoimmune diseases [ 44 ], and decreased fertility [ 45 ].…”
Section: Clinical Issuesmentioning
confidence: 99%
“…31 It has been suggested that women with below-recommended intakes of vitamin D may be less likely to conceive and might benefit from increased vitamin D intake to achieve adequate levels. 24…”
Section: Introductionmentioning
confidence: 99%
“…Não houve diferença entre os grupos múltiplos micronutrientes e ácido fólico no peso médio ao nascer (diferença média ajustada: 36,78; IC 95%:19,42 a 92,98 e p = 0,200), enquanto a suplementação com múltiplos micronutrientes reduziu significativamente as chances de bebês com baixo peso ao nascer (BPN) (ORA: 0,58; IC 95%: 0,36 a 0,11 e p= 0,019). Association of vitamin D intake and serum levels with fertility: results from the Lifestyle and Fertility Study Fung et al (2017) Avaliar o papel da ingestão de vitamina D e níveis séricos na confirmação de gravidez e ocorrência de nascidos vivos.…”
Section: Figura 1 Processo De Seleção Dos Artigos Incluídos No Estudounclassified
“…Estes autores observaram que as concentrações de vitamina D nesse grupo estavam diminuídas em relação aos níveis do grupo controle e postularam que o estado materno de vitamina D pode influenciar os desfechos da gravidez, podendo sua deficiência ocasionar o aborto. Fung et al (2017) desenvolveram um estudo prospectivo de coorte, com mulheres nulíparas entre 18 e 39 anos, que estavam tentando engravidar analisando a ingestão de vitamina D e sua correlação com a infertilidade. Após analisarem um grupo com 132 mulheres, concluíram que mulheres que apresentaram a ingestão de vitamina D abaixo da recomendação de necessidade média estimada para gestantes e níveis séricos de 25-hidroxivitamina D em risco de inadequação ou deficiência, apresentaram menos chances de engravidar, sendo que um aumento na ingestão de vitamina D pode ser benéfico, auxiliando em quadros de infertilidade.…”
Section: Yan Et Al (2017)unclassified